Education Policy on The Prohibition of Smoking In A Campus Environment - Dinil Abrar Sulthani; Kunaenih Kunaenih (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2020)
The existence of a smoking prohibition policy in the campus environment is the best effort in maintaining a good and conducive learning environment. The purpose of this study was to find out the response and a model for the prohibition of smoking. The research location at the Islamic University of Jakarta (UID), using the research method used by Research and Development (RnD). This development research will involve 18 respondents consisting of 6 lecturers/staff and 12 students with random respondents. The findings showed that 1) The response to the establishment of a smoking prohibition policy in the UID environment was still low. Does not reach more than more than 70% of the respondent’ answers. The model for a smoking prohibition policy that can be taken by university leaders is to hold various activities that support the go green program. As; stop smoking campaign, hold seminars or workshops, and add symbols that prohibit smoking in a campus environment.